Man, Meaning, and Mystery : 100 Years of History of Religions in Norway. The Heritage of W. Brede Kristensen - Kristensen, W. Brede 1867-1953.; Hjelde, Sigurd. (Numen Book Series, 2000)
At an international symposium in Norway, the 100 years' anniversary of the academic study of religion was celebrated. This volume contains the papers that were presented at this conference. A major part of the papers deals with the situation of this discipline around the turn of the last century, focussing especially on the work of the Dutch-Norwegian scholar W. Brede Kristensen (1867-1953) and on other founding fathers in the Scandinavian countries. Other contributors discuss methodological questions relating to the idea of a phenomenology of religion. Furthermore, an attempt is made to compare the study of religion at the end of the twentieth century with the situation a hundred years earlier, and to trace some of the lines of development. The book includes a bibliography of publications by W. Brede Kristensen.